Diagnostic progression to schizophrenia: A nationwide cohort study of 11 170 adolescents and young adults with autism spectrum disorder. Issue 12 (27th September 2022) - Hsu, Tien‐Wei; Chu, Che‐Sheng; Tsai, Shih‐Jen; Hsu, Ju‐Wei; Huang, Kai‐Lin; Cheng, Chih‐Ming; Su, Tung‐Ping; Chen, Tzeng‐Ji; Bai, Ya‐Mei; Liang, Chih‐Sung; Chen, Mu‐Hong
Abstract : Aims: Previous studies have suggested an increased risk of developing schizophrenia later in life in children with autism spectrum disorder (ASD). This study aims to investigate the diagnosis stability and the potential predictors for progression to schizophrenia in ASD. Methods: We recruited 11 170 adolescents (10–19 years) and young adults (20–29 years) with ASD between 2001 and 2010. They were followed up to the end of 2011 to identify newly diagnosed schizophrenia. The Kaplan–Meier method and Cox regression with age as a time scale were employed to estimate incidence rates and the significance of candidate predictors. Results: The progression rate from ASD to schizophrenia was 10.26% for 10 years of follow‐up. Among 860 progressors, 580 (67.44%) occurred within the first 3 years after a diagnosis of ASD. The identified predictors were age (reported as hazard ratio with 95% confidence interval: 1.13; 1.11–1.15), depressive disorder (1.36; 1.09–1.69), alcohol use disorder (3.05; 2.14–4.35), substance use disorder (1.91; 1.18–3.09), cluster A personality disorder (2.95; 1.79–4.84), cluster B personality disorder (1.86; 1.05–3.28), and a family history of schizophrenia (2.12; 1.65–2.74). Conclusion: More than two‐thirds of the progressors developed schizophrenia within the first 3 years. Demographic characteristics, physical and psychiatric comorbidities, and psychiatric family history were significant predictors of progression.